PERANAN BADAN PERMUSYAWARATAN DESA DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA MATA AIR KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Gelang, Fransiskus Jasnaida; Sonbay, Yolinda Yanti; Timuneno, Antonius Yohanes William (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2023)
In the current government era, the village plays an important role where the village is at the forefront of identifying any problems that exist in society. One way for the government to find out about problems in the community is to form a Village Consultative Body (BPD) so that people's aspirations can be recorded in the RAPBDes to make the APBDes. This study aims to find out how the process of preparing the APBDes is, what is the role of the BPD in preparing the APBDes, whether the role of the BPD in preparing the APBDes in Mata Air Village has been effective. This study uses qualitative methods and the types of data in this study are primary data and secondary data. The results of this study indicate that the process of preparing the APBDes in Mata Air Village consists of several stages, starting with the village head forming a team until the village head determines the RAPBDes to become Perdes APBDes and submits it to the Regent through the Camat to be ratified as APBDes. The role of the BPD in preparing the APBDes is to capture community aspirations through meetings and decisions taken by the BPD reflect the needs of the community and the cooperation between the BPD and related agencies is quite good, so that the programs implemented are in accordance with the needs of the community. The preparation of the APBDes in Mata Air village has been running effectively because the BPD has carried out their duties in accordance with their portion or function where they carry out the various products they produce including village regulations and supervision regarding the implementation of the APBDes.